Metamaterial fabrication using combined multiphoton polymerization and optical trapping - Askari, Meisam (2017)
Metamaterials are manmade structures with unique properties that cannot be found in nature. The metamaterial properties are structure dependent and enabled by the subwavelength periodic structure of the metamaterial. The goal of this thesis was to utilize an Additive Manufacturing (AM) technique to fabricate periodic metamaterial structures. Multi-Photon Polymerization (MPP) is a powerful AM method that has the capability to manufactures complex micro-scale 3D structures using ultra-short laser pulses. Typically, MPP has been used to manufacture micron-scale components in photopolymer materials. However, the development of sub-micron scale processes that can produce components from multiple materials within a single manufacturing step would be advantageous and open the potential to include different materials that can be manipulated and embedded within structures with sub-micron feature sizes.